Aboveground Carbon Fixation and Nutrient Retention in Temporary Spontaneous Cover Crops in Olive Groves of Andalusia - Torrús-Castillo, Milagros; Domouso, Pablo; Herrera-Rodríguez, José M.; Calero, Julio; García-Ruiz, Roberto (Frontiers in Environmental Science, 2022)
In Southern Spain, olive trees have traditionally been cultivated in marginal areas with relatively shallow and bare soils under rainfed conditions, resulting in heavy soil losses and soil degradation. The implementation of temporary spontaneous cover crops in the inter-rows of olive groves, has proven to be a suitable diversification strategy to reduce soil erosion but it can also contribute to climate change mitigation and the boosting of internal nutrient recycling. However, information on the contribution of cover crops to atmospheric CO2 fixation and on nutrient retention in olive groves is scarce, which is a major drawback when it comes to modelling on larger spatial scales. In this study, we aimed to assess the potential effects of temporary spontaneous cover crops in olive groves on CO2 fixation and nutrient retention. The aerial biomass of cover crops (0.25m2 frames) and contents of carbon and nitrogen (CNHS analyser), phosphorus and potassium (IPC-MS) were analyzed in 46 commercial olive groves with different tree densities and cover crop layouts; the whole farm (WCC), the whole farm except the area below the tree canopy (CCC) or in bands of a given width in the inter-row area (BCC). Cover crops of 56 % of the olive groves were under BCC whereas only 17% were under WCC. The annual net primary production of cover crops under WCC (1,707.4 kg DW ha-1 y-1) was significantly higher than that of CCC (769.5 kg DW ha-1 y-1) and with intermediate values for BCC (1,186.4 kg DW ha-1 y-1). Similarly, the annual rate of C-CO2 fixation in the annual net primary production of olive groves with WCC (642.1 kg C ha-1 y-1) was 1.35 and 2.1 times higher than the olive groves with BCC and CCC, respectively. On average, 19.5 kg N ha-1 y-1, 2.48 kg P ha-1 y-1 and 24.30 kg K ha-1 y-1 was accumulated in the biomass of the cover crops. This study demonstrates that cover crops contribute significantly to CO2 reduction and the retention of significant amounts of tree-unused nutrients. In addition, the higher the area covered by cover crops, the higher the contribution to these ecosystem services.